2015
DOI: 10.1111/jhn.12307
|View full text |Cite
|
Sign up to set email alerts
|

Individualised dietary counselling for nutritionally at‐risk older patients following discharge from acute hospital to home: a systematic review and meta‐analysis

Abstract: Individualised dietary counselling by dietitians following discharge from acute hospital to home improved BW, as well as energy and protein intake, in older nutritionally at-risk patients, although without clearly improving physical function. The effect of this strategy on physical function and other relevant clinical outcomes warrants further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
54
0
5

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 33 publications
6
54
0
5
Order By: Relevance
“…Further research should explore not only the community resources available, but also the process for referral and barriers to care that occur, especially because quality transition care and interventions initiated in hospital and continued in the community can improve outcomes, including nutritional status . However, communication and continuation of care is a known problem with any transition .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further research should explore not only the community resources available, but also the process for referral and barriers to care that occur, especially because quality transition care and interventions initiated in hospital and continued in the community can improve outcomes, including nutritional status . However, communication and continuation of care is a known problem with any transition .…”
Section: Discussionmentioning
confidence: 99%
“…Further research should explore not only the community resources available, but also the process for referral and barriers to care that occur, especially because quality transition care and interventions initiated in hospital and continued in the community can improve outcomes, including nutritional status (13)(14)(15)(16)(17)(18)(19)(20)(21) . However, communication and continuation of care is a known problem with any transition (22)(23)(24) . This large multicentre cohort study has provided an opportunity to investigate, for the first time, which patient factors are associated with dietetic care post discharge from hospital, yet there are also limitations to this work.…”
Section: Discussionmentioning
confidence: 99%
“…Nutrition-focused interventions, such as dietary counselling and oral nutrition supplementation (ONS), have demonstrated success in improving outcomes after discharge (15)(16)(17) . Systematic reviews/meta-analyses have found that dietary counselling and ONS improve energy intake and weight gain, although they have a limited impact on mortality (18)(19)(20)(21)(22)(23)(24) . It is likely that these interventions are valuable components of post-discharge care that includes additional intervention such as discharge planning and care management.…”
Section: Introductionmentioning
confidence: 99%
“…Another study involving six patients following similar surgery outlined a need for tailored professional counselling which links with support provided by family and social networks (Washington, 2016). Provision of counselling focusing on individualised dietary advice and intake has been shown to improve outcomes for patients in the acute care setting (Cheung, Pizzola, & Keller, 2013;Munk et al, 2016).…”
Section: E809mentioning
confidence: 99%